1966
DOI: 10.1021/jf60144a016
|View full text |Cite
|
Sign up to set email alerts
|

Residue Determination, Colorimetric Determination of Abate Residues from Several Environmental Conditions

Abstract: A colorimetric method for residues of Abate insecticide, OjOjO'jO'-tetramethyl-OjO'thiodi-p-phenylene phosphorothioate, is based on its hydrolysis to 4,4/-thiodiphenol and subsequent determination at 485 m^after reaction with 4-aminoantipyrine and periodate. Procedures are described for natural waters, mud, oysters, rice grain, and rice foliage. Recoveries and apparent Abate insecticide concentrations in control tissues are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

1968
1968
1984
1984

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…The average recovery of Abate from water by this method was 98.5 ± 1.3 %. These data are in good agreement with the partition distribution of Abate between hexane and methanol-water shown by Blinn and Pasarela (1966). Water fortified with Abate at 0.12 p.p.m.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The average recovery of Abate from water by this method was 98.5 ± 1.3 %. These data are in good agreement with the partition distribution of Abate between hexane and methanol-water shown by Blinn and Pasarela (1966). Water fortified with Abate at 0.12 p.p.m.…”
Section: Discussionsupporting
confidence: 88%
“…Several methods have been proposed for determination of Abate residues, none of which are completely satisfactory for determination at the low levels encountered in the treatment of potable waters. A colorimetric method for determination of Abate residues by Blinn and Pasarela (1966) was based on the reaction of the hydrolysis product, 4,4-thiodiphenol, with 4-aminoantipyrine andperiodateand subsequent determination at 485 µ. In the method of St. John and Lisk (1968), the methylated alkyl phosphate hydrolytic product of Abate was determined, using a gas chromatograph equipped with a thermionic detector.…”
mentioning
confidence: 99%
“…Bowman et al (1968) have shown that Abate adsorbs readily on to surfaces and thereby forms a natural slow-release system which resists metabolic breakdown. This is supported by observations in artificial ' mini-ecosystems ' (Blinn & Pasarela, 1966) and in natural ponds (Bowman & Orloski, 1966) where unchanged Abate was still present one week after application. The only available iield data on the absorption of Abate by aquatic organisms (Fitzpatrick & Sutherland, 1976) showed that salt marsh snails exposed to fortnightly treatments with Abate granules at 0.1 12 kg a.i.…”
Section: P M a T T I L I E S S E N A N D J S J O H N S O Nsupporting
confidence: 68%
“…Before Abate insecticide could be used commercially, data concerning its residual behavior in natural waters and adjacent mud were acquired for registration purposes (Bowman and Orloski, 1966). The residue analytical procedure used for this study was designed to respond only to the parent compound since a preliminary metabolic study of this material in natural waters, mud, and bean plants using nonradiotracer techniques showed little evidence of any postulated metabolic degradation products (Blinn and Pasarela, 1966). The desirability of using Abate insecticide to control mosquito larvae in food-producing areas and to control several insect pests of food crops has required additional residue studies and the detailed evaluation of the metabolic fate of Abate insecticide in a typical plant environment.…”
mentioning
confidence: 99%